Hišni arhiv Slovenskega etnografskega muzeja - Serec, Anja (Etnolog. Nova vrsta (Ljubljana), 2003)
The article presents the House Archive which is part of the documentation of the Slovene Ethnographic Museum. It deals with the archivećs structure, how it is arranged, processed, and preserved. Presenting the system that is used, the article explains the structure of the archive's contents. The scope of information provided by the House Archive and the options to use it, for instance, in presentations, are illustrated. Three separate House Archives are presented in detail.
Keywords: Slovenski etnografski muzej; Ljubljana; ethnology; etnologija; dokumentacija; arhivi; cultural heritage; kulturna dediščina